PROFIL LIPOPROTEIN DAN KADAR KOLESTEROL TOTAL SERUM AYAM YANG DIBERI SUPLEMENTASI KHITOSAN (THE EFFECT OF CHITOSAN SUPPLEMENTATION TO THE LIPOPROTEIN PROFILE AND TOTAL SERUM CHOLESTEROL LEVEL OF CHICKEN) - Sari Nindhia, Tjokorda; Werdi Susari, Ni Nyoman; Suarsana, I Nyoman (Jurnal Veteriner, 2007)
This research was carried out to evaluate the effect of chitosan supplementation in the chicken food with high cholesterol diet on total cholesterol level and serum lipoprotein profile of chicken. The aims of this study were to evaluate the effects of chitosan supplementation on lipid level, total cholesterol, triglyceride, High density lipoprotein (HDL), Very low density lipoprotein (VLDL) and Low density lipoprotein (LDL) concentration on serum chicken. The experimental design used in this study was completely randomized design with 4 treatment groups. Group K (as a controlled without cholesterol er and chitosan), group A (treated with cholesterol 1% without chitosan), group B (treated with cholesterol 1% and chitosan 15%) and group C (treatment with cholesterol 1% and chitosan 30%). The results showed that treatment with egg yolk powder (group A) could cause hyperlipydemia on chickens and cholesterol total was significantly different (p<0,05) compared to group K (control). Treatment with 30% chitosan were reducing lipid concentration, cholesterol total, triglyceride, VLDL and LDL serum of chicken, respectively (p<0,05) compared to group A (egg yolk powder without chitosan), total HDL concentration was not significantly different (P>0,05).  It was concluded that the suplementation of 30% chitosan in the chicken food could reduce total serum cholesterol level in hyperlipydemia chicken.
Keywords: Chitosan, cholesterol,? lipoprotein,? chicken serum